Mass Spectrometry-Based Proteomics for Investigating DNA Damage-Associated Protein Ubiquitylation - Heidelberger, Jan B.; Wagner, Sebastian A.; Beli, Petra (Frontiers in Genetics, 2016)
Modification of proteins with the 76 amino acid protein ubiquitin plays essential roles in cellular signaling. Development of methods for specific enrichment of ubiquitin remnant peptides and advances in high-resolution mass spectrometry have enabled proteome-wide identification of endogenous ubiquitylation sites. Moreover, ubiquitin remnant profiling has emerged as a powerful approach for investigating changes in protein ubiquitylation in response to cellular perturbations, such as DNA damage, as well as for identification of substrates of ubiquitin-modifying enzymes. Despite these advances, interrogation of ubiquitin chain topologies on substrate proteins remains a challenging task. Here, we describe mass spectrometry-based approaches for quantitative analyses of site-specific protein ubiquitylation and highlight recent studies that employed these methods for investigation of ubiquitylation in the context of the cellular DNA damage response. Furthermore, we provide an overview of experimental strategies for probing ubiquitin chain topologies on proteins and discuss how these methods can be applied to analyze functions of ubiquitylation in the DNA damage response.